Medicinal plants with folkloric uses in the management of Breast Cancer in Northwestern Nigeria: A Cross-sectional survey - Danladi , Suleiman; Ibrahim, Umar Idris; Mohammed, Khalid Garba; Lawal, Basira Kankia; Mohammed, Aisha; Mas’ud, Idris Aliyu; Abubakar, Nazifi Auwalu; Alhassan, Aisha Muhammad; Bello, Sani Sa’idu (Ethnobotany Research and Applications, 2025)
Background: The ethnobotanical use of medicinal plants for the treatment of breast cancer is widely practiced in north-western Nigeria. While their pharmaceutical potential is often explored, this study prioritizes the cultural significance and traditional knowledge surrounding plant use by local healers. This study aimed to document and analyse the knowledge, practices, and cultural contexts in which traditional medicinal plants are used for breast cancer management in three states of north-western Nigeria. Methods: An ethnobotanical survey using structured interviews was conducted among 154 traditional medicine practitioners and herb sellers across Kano, Katsina, and Kebbi. Data were analysed using descriptive statistics and multivariate techniques, including cluster and correspondence analyses, to identify patterns in plant use. Results: A total of 80 plant species from 34 families were documented, with Fabaceae being the most cited. Key species included Guiera senegalensis, Cassia singueana, and Boswellia odorata. Leaves and bark were the most frequently used parts. Cluster analysis revealed distinct usage patterns by geography and healer type. Though few healers reported ritualistic practices, these traditions were often embedded in their healing philosophies. Correspondence analysis showed a strong association between plant part and administration route. Conclusion: The study highlights the rich ethnobotanical knowledge of traditional healers in north-western Nigeria. While biomedical interest may view these plants for drug discovery, their cultural roles and ritual uses highlights the importance of preserving indigenous knowledge systems. Further interdisciplinary research is encouraged to integrate ethnobotany with cultural anthropology and health policy. Keywords: Medicinal plants; Breast-cancer; Survey; Traditional medicine; Northwest, Nigeri